Analisis Strategi Mutu Produk Indomie Untuk Memenuhi Standarisasi Pasar Global - Suhairi, Suhairi; Hayatunnufus, Annisah Fildzania; Utami, Annisa Dwi; Lubis, Listiya Andana; Putri, Tasya Yustika (LPPM Universitas Labuhanbatu, 2022)
The purpose of this research is to find out how Indomie's product quality strategy can be analyzed to meet global market standards. Qualitative research is used as a research method, namely: 1) descriptive and explorative; 2) describe and explain. Based on the discussion, it can be concluded that an analysis of Indomie's product quality strategy to meet global market standards can be carried out through 1) Production strategy, carrying out continuous innovation, building factories overseas, product standardization and quality maintenance. 2) Location determination strategy, taking into account distribution channels, sales areas, storage locations, inventory levels and locations and transportation systems. 3) Promotional strategy, Indomie has a slogan that is very simple but suitable and easy for people to remember, namely,